Description of Stegelletina lingulata sp. n. (Nematoda, Rhabditida, Cephalobidae) from xeric environments in Iran - Abolafia, Joaquín; Shokoohi, Ebrahim (Zootaxa, 2017)
A new species belonging to the genus Stegelletina, S. lingulata sp. n., is described from xeric natural areas from Iran. It is characterized by having small body (0.51–0.69 mm in females and 0.45–0.64 mm in males), cuticle slightly tessellated especially at anterior end, lateral field with three longitudinal incisures, lips with long acute process at primary axils and three more dentate processes at secondary axils, primary axils with one triangular axillar guard process and secondary axils lacking axillar processes, labial probolae long (9–11 µm) with slender peduncle lacking adaxial expansion and with convergent smooth prongs, stoma, pharynx and reproductive systems cephaloboid, excretory pore at isthmus level, spermatheca 1.1–1.4 times, and post-vulval sac 0.9–1.2 times the corresponding body diameters in length, female rectum 0.6–0.8 times anal body diameter long, female tail conoid (35–47 µm long, c = 14.0–15.6, c' = 2.1–2.7) with fine rounded terminus, male tail conoid, curved ventrad (53–59 µm long, c = 11.0–12.0, c' = 1.9–2.5) with rounded terminus, spicules 31–33 µm long with ventrally straight manubrium and gubernaculum 14–17 µm long. Measurements and illustrations (line drawings, LM and SEM) are provided for this species. In addition, comments on the morphology of the lip region of the species of the genus Stegelletina are included.